(untitled) (Journal Of Educational and Psychological Researches, 2022)
The research aims to identify the effect of teaching according to the augmented reality on the technique of the visual thinking skills among scientific fifth-grade students in a biology course. In order to achieve the goal of the research, the researcher adopted the experimental approach with the partial set of the two equal groups with the dimensional test of visual thinking skills, The research population represented all the scientific students of the fifth grade for morning government schools affiliated to the General Directorate of Education of Baghdad / Karkh II, alshakerin preparatory for boys was chosen intentionally, in which two groups were chosen for this study, one group is chosen randomly as the control group via lottery, whereas the other group is chosen to be as the experimental group. The total number of students are (53) students by (26) students are chosen for the experimental group that were taught according to the augmented reality technique. The other group is the control group consisting of (27) students that were taught according to the traditional way. The results showed there is statistically a significant difference for the experimental group in the visual thinking skills test.